Effect of Acute Persadia Gymnastic on The Ability to Concentrate in Diabetic Patients - Desi Rianti Rahmadhani; Lilik Herawati; Sony Wibisono Mudjanarko; Kristanti Wanito Wigati; Laylatul Fitriah Mukarromah; Winna Adelia Amru (Surabaya Physical Medicine and Rehabilitation Journal, 2022)
Background: Diabetes Mellitus (DM) can affect the peripheral and central nervous system. It can affect cognitive function, one of which can be seen from the decrease in the concentration ability. The concentration ability can be assessed by measuring the reaction time. Reaction time is the time interval between the onset of a stimulus and the initiations of a response. One of the important treatments for DM is physical exercises. Persadia gymnastic is one example of physical exercise that is specially designed for people with DM.Aim: The purpose of this study was to identify the effect of acute Persadia gymnastic on the concentration ability of people with DM.Material and methods: This was an experimental study in type 2 DM patients. Fourteen subjects who met the inclusion criteria were analyzed and randomly grouped into the control (without performing Persadia gymnastic) and the intervention group (performing Persadia gymnastic). The subject’s reaction times were measured before and after the intervention. The mean results of the reaction time of all subjects were then compared between the control and the intervention groups using the Independent-T test and Mann-Whitney tests.Result: The analyzed data were only 7 subjects per group with a total of 14 subjects. The mean value of reaction time in the intervention group was decreased, both audio (-0.04 ± 0.85) and visual (-0.09 ± 0.56). However, there was no significant difference of the reaction time between control and intervention groups (p > 0.05).Conclusions: Many factors can affect reaction time and some still cannot be controlled in this study due to a lot of limitations. Further research is still needed to figure out the effect of persadia gymnastics on the ability to concentrate in people with Diabetes Mellitus.